Crystal structure, microstructure and electrical properties of (1-x-y)Bi0.5Na0.5TiO3-xBi0.5K 0.5TiO3-yBiFeO3 ceramics near MPB prepared via the combustion technique - Sumang, Rattiphorn; Vittayakorn, Naratip; Bongkarn, Theerachai (My University, 2013)
(1-x-y)Bi0.5Na0.5TiO3-xBi 0.5K0.5TiO3-yBiFeO3 (BNKFT-x/y with 0.12≤x≤0.24, 0≤y≤0.07) lead-free piezoelectric ceramics have been prepared by the combustion technique. The effects of amounts of x and y on structures and electrical properties were examined. Powders and ceramics can be well calcined and sintered at 750 °C for 2 h and 1025-1050 °C, respectively. The results indicated that the crystalline structure and microstructure changed with the increase of x and y concentrations. XRD results of BNKFT-x/0.03 and BNKFT-0.18/y ceramics with 0.12≤x≤0.24 and 0≤y≤0.07 showed the rhombohedral-tetragonal morphotropic phase boundary (MPB). The addition of y caused a promoted grain growth while the addition of x suppressed the grain growth. The highest density (ρ=5.85 g/cm3), superior dielectric properties at Tc (εr=7846 and tan δ=0.02), remnant polarization measured at 40 kV/cm (Pr = 20.1 μC/cm2) and piezoelectric coefficient (d33=213 pC/N) were obtained for x=0.18 and y=0.03. © 2012 Elsevier Ltd and Techna Group S.r.l.
Keywords: (1-x-y)Bi0.5Na0.5TiO3-xBi0.5K 0.5TiO3-yBiFeO3; C. Dielectric properties; C. Ferroelectric properties; D. Perovskite